Picture Perfect - Picoult, Jodi (London Hodder & Stoughton Ltd, 2010)
What do you do when the person who holds you together is the one who tears you apart? Jodi Picoult's compelling number one bestseller centres on domestic abuse.
Keywords: Women anthropologists -- California -- Marital conflict -- Actors -- Married people -- Abused wives